Douglas Waddell Jolly (1904–1983) – New Zealand pioneer of modern battlefield surgery. (November 2020) - Derby, Mark; Lowe, David
New Zealand-born surgeon Douglas Jolly was studying in London at the outbreak of the Spanish Civil War. He joined a British volunteer medical team and in December 1936 was placed in charge of a mobile medical unit of Spain's Republican Army. For the following two years, he took part in every major battle of the war, operating as close as possible to the front line. In that time he made significant contributions to trauma surgery, especially for abdominal injuries, and developed a 'three-points-forward' triage system. He described these medical innovations in a handbook which became highly influential among Allied medical services in Second World War, Korea and Vietnam. Jolly served with the Royal Army Medical Corps (RAMC) in the Middle East during Second World War and was awarded a military OBE.After the war, he became Chief Medical Officer of Queen Mary's Orthopaedic Hospital, Roehampton. He has been described as 'a pioneer in the field of surgical treatment for trauma and one of the most notable war surgeons of the 20th century.' In belated local recognition of this innovative and dedicated pioneer of trauma surgery, a memorial to Jolly will be unveiled in his home town of Cromwell, New Zealand in 2018.